Kompleksitas Perubahan Hutan Mangrove Pada Kawasan Pesisir Kedungsepur - Widjonarko Widjonarko; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2025)
Mangrove forests in the coastal area of the Kedungsepur National Strategic Area play a crucial role in ecosystem services in coastal areas. Mangrove forests support the provisioning ecosystem services, regulating ecosystem services, supporting ecosystem services, and cultural ecosystem services. However, with the development of human activity systems and environmental changes, the existence of mangrove forests in coastal areas has been disrupted, resulting in changes in their spatial patterns. Changes in the area of mangrove forests in the Kedungsepur coast have placed significant pressure on regulatory ecosystem services, particularly protection from coastal erosion and tidal flooding, pressure on food supply ecosystem services, and cultural ecosystem services, namely the provision of adequate housing for coastal communities..